Does it pay firms to register for taxes? The impact of formality on firm profitability - David McKenzie; Yaye Seynabou Sakho (Institute for the Study of Labor (IZA), 2007)
This paper estimates the impact of registering for taxes on firm profits in Bolivia, the country with the highest levels of informality in Latin America. A new survey of micro and small firms enables us to control for a rich set of measures of owner ability and business motivations that can affect both profits and the decision to formalize. We identify the impact of tax registration on business profitability using the distance of a firm from the tax office where registration occurs, conditional on the distance to the city center, as an instrument for registration. Proximity to the tax office provides firms with more information about registration, but is argued to not directly affect profits. We find tax registration leads to significantly higher profits for the firms that the instrument affects. However, we also find evidence of heterogeneous effects of tax formality on profits. Tax registration is found to increase profits for the mid-sized firms in our sample, but to lower profits for both the smaller and larger firms, in contrast to the standard view that formality increases profits. We show that owners of large firms who have managed to stay informal are of higher entrepreneurial ability than formal firm owners, in contrast to the standard view (correct among smaller firms) that informal firm owners are low ability.
Keywords: O17; 330; Informal sector; entrepreneurial ability; tax registration; Informeller Sektor; Steuererhebung; Ertragsteuer; Bolivien